Office Management of Chemical Dependency by Family Physicians: The role of the physician in treating chemical dependency - Baker, Ray (1991)
Family physicians are in an ideal position to identify, intervene with, and treat substance use disorders. If family physicians position themselves to reflect objective evidence of consequences of substance use and offer suggestions for change while leaving responsibility for recovery with the patient, patients often choose to recover. Because the disease is characterized by exacerbations, remissions, and relapses, continued involvement with the recovering patient ensures the greatest chance of recovery.